Exploring the experiences of people with the dual diagnosis of acquired brain injury and mental illness - Cocks, Errol; Bulsara, C.; O'Callaghan, Annalise; Netto, Julie; Boaden, Ross (Informa UK Limited, 2014)
Primary objective: People with the dual diagnosis of acquired brain injury and mental illness (ABI/MI) are vulnerable to a range of negative life experiences, which has received limited attention in the literature. The objective of the project described in this paper was to identify and describe these experiences in order to distinguish barriers and facilitators to successful rehabilitation and recovery.Research design: The project used qualitative methodologies. Methods and procedures: The 15 participants were eight people with ABI/MI, two family members and five support workers. Nineteen interviews were conducted. Analysis of these interviews produced a set of five key themes, with each theme elaborated by a set of descriptive issues.Main outcomes and results: The five themes were loss, personal development, occupation, family and services. The experiences of people with ABI/MI were strongly negative. They faced more barriers than facilitators to recovery. Current policies and practices were inadequate.Conclusions: Enhanced stakeholder collaboration and co-ordination and a more individualized, long-term perspective on the needs of people with ABI/MI are recommended to guide future policy and practice. Future research on quality-of-life, wellbeing, community inclusion and participation in ordinary life was recommended.